Environmental Impacts of Selenium in Chinese Soil on Traditional Chinese Medicinal Plants and Human Health - Ying Pan; Waqar Ali; Muhammad Shafeeque; Kang Mao; Wei Li; Hua Zhang (Water, Air, & Soil Pollution, 2026)

Comparative study on techno-functional properties in popped millets and pseudocereals - Yashi Srivastava; Twinkle Kesharwani; Muhammad Shafeeque; Aleena Ebrahim (Vegetos, 2026)

Evaluation and progression of marine heatwaves over the northwestern Indian Ocean: A comparative study using satellite and numerical model data - Akurathi Venkata Sai Chaitanya; Abdul Azeez Saleem; Muhammad Shafeeque; Salim Lateef; Mohamed Asharaf; Jiya Albert (Regional Studies in Marine Science, 2026)

Spatiotemporal lag effects between vegetation dynamics and climate variability on the Tibetan Plateau during 2001–2024 - Zulqarnain Satti; Yipeng Wang; Peng Shen; Muhammad Naveed; Muhammad Burhan Memon; Muhammad Shafeeque; Chong Fan; Heifeng Li (Remote Sensing Applications: Society and Environment, 2026)

Geochemical dynamics and risk assessment of multi-metal contamination in alluvial soil–rice ecosystems of Pakistan - Waqar Ali; Muhammad Shafeeque; Muhammad Salam; Kang Mao; Muhammad Wajahat Aslam; Hua Zhang; Wei Li (Journal of Environmental Chemical Engineering, 2026)

Arsenic speciation and biogeochemical cycling in Pakistan's alluvial rice ecosystem: Health and trade implications - Waqar Ali; Muhammad Shafeeque; Muhammad Salam; Kang Mao; Muhammad Wajahat Aslam; Sehrish Fatima; Hua Zhang; Wei Li (Environmental Pollution, 2026)

Evaluation of the near-surface wind products from reanalyses over the North-Western Indian Ocean - Akhil Varghese; Phiros Shah; Akash S; Athuldev A V; Prince Arayakandy; Muhammad Shafeeque; Sruthi Thalayappil R S (Ocean Dynamics, 2026)

Sediment transport modeling of trenching activities: a case study for the Safaniya coastal waters in the Arabian Gulf - Abdul Azeez Saleem; Akurathi V. S. Chaitanya; Salim Lateef; Jiya Albert; Muhammad Shafeeque; Karuppasamy P. Manikandan; Thadickal V. Joydas; Mohamed Asharaf; Luai M Alhems; Ali M. Qasem; Sabique Langodan; Diego Lozano-Cortés (Ocean Dynamics, 2026)

Development of leaching agents and mechanisms for rare earth element leaching from ion adsorption clay - Shafeeque Ahmed; Abdulhalim Shah Maulud; Muhammad Nawaz; Mohamad Azmi Bustam (Sustainable Chemistry and Pharmacy, 2025)

Chlorophyll-a modulation in the Arabian Gulf using two decades of merged ocean-color data - Muhammad Shafeeque; Abdul Azeez Saleem; Akurathi V. S. Chaitanya; C. P. Abdulla; Salim Lateef; Jiya Albert (Frontiers in Marine Science, 2025)
Introduction The Arabian Gulf (Gulf) is a dynamic marine ecosystem in which phytoplankton productivity, indicated by Chlorophyll- a (Chl- a ), is strongly affected by environmental and climatic variables. Understanding the spatiotemporal variability of Chl- a and its driving environmental factors is critical for assessing primary productivity and ecosystem dynamics of the Gulf. Methods This study investigated the long-term Chl- a variability and its dynamic response to environmental variables in the Gulf using two decades (2003 to 2023) of Chl- a data from merged multi-sensor Ocean Colour Climate Change Initiative. We adopted an integrated approach that includes climatology, multivariate statistical analysis, interannual variability and trend analysis to evaluate Chl- a variability and identify its dominant drivers. Results Seasonal climatology exhibited a marked winter bloom driven by convective mixing and nutrient replenishment, followed by a summer decline due to strong stratification. Box average analysis using correlogram and principal component analysis for selected regions revealed distinct regional patterns, with the northern and central Gulf showing higher variability. The results further highlighted sea surface temperature (SST), sea surface salinity, photosynthetically available radiation and wind speed as primary drivers of Chl- a variability in the Gulf. The interannual variability of Chl- a peaks along the central eastern Gulf in winter and central western Gulf during summer, highlighting regional heterogeneity in phytoplankton dynamics. Long-term spatial trend analysis of Chl- a , net primary productivity (NPP) and SST indicated overall decreasing trend in Chl- a and NPP, particularly along the north and eastern coasts of the Gulf; and warming SST in the northern and central Gulf. Discussion The results indicate the requirement of further research on the complex interplay between physical and biogeochemical factors, and anthropogenic influences on Chl- a distribution, which can help future monitoring and predictive ecosystem models for the Gulf under changing climate conditions.

Studies of rheological properties of edible gel material extracted from common millets in India - Yashi Srivastava; Muhammad Shafeeque; Manpreet Kaur; D. C. Saxena (Vegetos, 2025)

Contamination and risk assessment of Thallium in the alluvial paddy rice soil system of Pakistan - Waqar Ali; Kang Mao; Muhammad Shafeeque; Muhammad Wajahat Aslam; Hua Zhang; Wei Li (Environmental Research, 2025)

Phenology of coastal upwelling in the Southeastern Arabian Sea: Insights from in-situ and satellite observations - Shirin J Jadhav; Muhammad Shafeeque; V S Arun; N N S Vishnu; B R Smitha (Journal of Earth System Science, 2025)

Cold snaps in Indian coastal waters: a critical threat to nursery rearing of juvenile silver pompano (Trachinotus blochii) in marine cages - Suresh Babu Padinhate Purayil; Grinson George Padinjakara; Muhammad Shafeeque; Jagannath Rathod; Praveen Narayan Dube; Mahendra Pal; Gopalakrishnan Achamveetil (Environmental Biology of Fishes, 2025)

Assessing the sustainability of threadfin bream fishery along South-eastern coast of the Arabian Sea: A comprehensive analysis of climate change impact and fishing frontiers - Radhika Balachandran; P.U. Zacharia; G.B. Purushottama; K.S. Sudarsan; Muhammad Shafeeque; R. Ratheesh Kumar; Eldho Varghese; Alphonsa Joseph; R. Rahul; Nanda Kishore; Rose P. Bright; P.K. Seetha; et al. (Regional Studies in Marine Science, 2024)

Effects of selenium on biogeochemical cycles of cadmium in rice from flooded paddy soil systems in the alluvial Indus Valley of Pakistan - Waqar Ali; Kang Mao; Muhammad Shafeeque; Muhammad Wajahat Aslam; Wei Li (Science of The Total Environment, 2024)

Investigating the impact of climate change on trend shifts of vegetation growth in Gilgit Baltistan - Zulqarnain Satti; Muhammad Naveed; Muhammad Shafeeque; Lanhai Li (Global and Planetary Change, 2024)

Quantifying future water-saving potential under climate change and groundwater recharge scenarios in Lower Chenab Canal, Indus River Basin - Muhammad Shafeeque; Mohsin Hafeez; Abid Sarwar; Arfan Arshad; Tahira Khurshid; Muhammad Irfan Asim; Shoaib Ali; Adil Dilawar (Theoretical and Applied Climatology, 2024)
Quantifying water-saving potential (WSP) is crucial for sustainable water resource management in canal command areas and river basins. Previous studies have partially or fully ignored the importance of groundwater in WSP assessments, particularly in irrigated areas. This study is aimed at quantifying WSP in the Lower Chenab Canal (LCC) command area of the Indus River Basin, Pakistan, under various scenarios of future climate change and groundwater recharge. These quantifications are conducted using an empirical model based on the Budyko theory. The model was forced using observed, remote sensing, and CMIP6 future climate data for two Shared Socioeconomic Pathways (SSP245 and SSP585) and their ensembles (cold-dry, cold-wet, warm-dry, and warm-wet) for possible futures. The results showed that the average WSP in the LCC command area was 466 ± 48 mm/year during the historical period (2001–2020). The WSP is projected to decrease by – 68 ± 3% under the warm-dry ensemble scenario (SSP245 and SSP585) and – 48 ± 13% under the ensembled cold-wet scenario by 2100. The results also demonstrated that WSP could be increased by up to 70 ± 9% by artificially recharging 20% of the abstracted groundwater per year in the LCC command area by the late twenty-first century. Our findings highlight the importance of adopting artificial groundwater recharge to enhance the WSP and sustainably manage water resources in the LCC command area. Policymakers should consider these findings when deciding on water resource management in the Indus River Basin.

Assessment of climate change impacts on glacio-hydrological processes and their variations within critical zone - Muhammad Shafeeque; Yi Luo; Arfan Arshad; Sher Muhammad; Muhammad Ashraf; Quoc Bao Pham (Natural Hazards, 2023)

Effects of climate change on vegetation and snow cover area in Gilgit Baltistan using MODIS data - Zulqarnain Satti; Muhammad Naveed; Muhammad Shafeeque; Sikandar Ali; Farkhod Abdullaev; Tauseef Muhammad Ashraf; Muhammad Irshad; Lanhai Li (Environmental Science and Pollution Research, 2022)

Upper layer characteristics of the South Eastern Arabian Sea associated with an unusual low saline pool during fag end of southwest monsoon - S Vishnu Narayanan Nampoothiri; Muhammad Shafeeque; V S Arun; B R Smitha; Kusum Komal Karati; K Rasheed; C R Asha Devi; Hashim Manjebrayakath (Journal of Earth System Science, 2022)

Spatio-temporal variability of chlorophyll- a in response to coastal upwelling and mesoscale eddies in the South Eastern Arabian Sea - Muhammad Shafeeque; A. N. Balchand; Phiros Shah; Grinson George; Smitha B. R.; Eldho Varghese; Ajith K. Joseph; Shubha Sathyendranath; Trevor Platt (International Journal of Remote Sensing, 2021)

Assessment of trace elements in urban topsoils of Rawalpindi-Pakistan: a principal component analysis approach - Muhammad Tahir Shehzad; Ghulam Murtaza; Muhammad Shafeeque; Muhammad Sabir; Haq Nawaz; Muhammad Jamal Khan (Environmental Monitoring and Assessment, 2019)

A Holistic Approach to Upwelling and Downwelling along the South-West Coast of India - Phiros Shah; R. Sajeev; K. J. Thara; Grinson George; Muhammad Shafeeque; S. Akash; Trevor Platt (Marine Geodesy, 2019)

Comparison of Seasonal Cycles of Phytoplankton Chlorophyll, Aerosols, Winds and Sea-Surface Temperature off Somalia - Muhammad Shafeeque; Shubha Sathyendranath; Grinson George; Alungal N. Balchand; Trevor Platt (Frontiers in Marine Science, 2017)

Quality of tube well water intended for irrigation and human consumption with special emphasis on arsenic contamination at the area of Punjab, Pakistan - Atta Rasool; Tangfu Xiao; Abida Farooqi; Muhammad Shafeeque; Yizhang Liu; Muhammad Aqeel Kamran; Ioannis A. Katsoyiannis; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)